Middle East and North Africa Data Book, September 2014 - Devarajan, Shanta; Mottaghi, Lili (Washington, DC: World Bank Group, 2014)
The Middle East and North Africa (MENA) data book serves as a quick reference and a reliable dataset for monitoring economic and social developments in the region. The data are drawn from the 2014 World Bank's World Development Indicators (WDI) and International Monetary Fund's (IMF's) direction of trade statistics. It contains macroeconomic, sectoral, and social indicators for 19 countries in the MENA region and aggregates for other developing regions. The data book presents following topics: basic indicators; national and fiscal accounts; trade; infrastructure; and human development.